London and the English desert – the geography of cultural capital in the UK - Dorling, D; Hennig, B (Routledge, 2015)
People in the UK and especially the English have become culturally attuned to seeing and experiencing a geography of extreme inequality as normal. Occasionally, new statistics are produced that show these gross inequalities in a new light and which then cause some shock. This was the case in 2013 when a report on arts funding highlighted just how concentrated such funding was within London, but we should not be so shocked by such a finding. It turns out that what that report really showed was a continuation of a now long established trend in which London gains more and more of the cake, a slight thicker slice each year as compared to the year before.